A TRANSLATION ANALYSIS OF ENGLISH SLANG WORDS IN THE NOVEL “SHINE” BY JESSICA JUNG - Ramadhan, Taufiq Brahmantyo Lintang; Jumanto, Jumanto (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
This research is entitled “A Translation Analysis of English Slang Words in the Novel Shine by Jessica Jung”. This research purpose is to analyze the types of slang words, types of translation techniques, and the dominantly used translation technique in translating slang words in the novel Shine by Jessica Jung. For the type of slang words, the researcher using Allan and Burridge theory meanwhile for the type of translation technique the researcher using Molina and Albir theory. For this research, the researcher found 70 data and it used descriptive qualitative method to analyze. The analysis shows that there are 5 types of slang words such as 67,1% (47 data) are Flippant slang words, 11,4% (8 data) are Fresh and Creative slang words, 8’6% (6 data) are Imitative slang words, 7,1% (5 data) are Acronyms slang words, and 5,8% (4 data) are Clipping slang words. Researcher also found 5 types of translation technique such as 75,8% (47 data) are Discursive Creation, 11,4% (8 data) are Established Equivalent, 5,8% (4 data) are Total Reduction, 4,2% (3 data) are Pure Borrowing, and 2,8% (2 data) are Borrowing Naturalized. Based on analysis, the most common type of translation technique that found in translating novel Shine by Jessica Jung is Discursive Creation with 75,8%. The reason is because there are a lot of unique writing styles such as slang words on novel that makes a different translation from the original meaning.